The liquidity reserve funding and management strategies - Thomas Heidorn; Christian Buschmann (Frankfurt School of Finance & Management, 2014)
This paper investigates the managing strategies of a bank's liquidity reserve in the broader context of the role of asset-liability management according to the liquidity issues of a banking organisation. Several types of liquidity are presented and how these are interconnected and how they might affect a financial institution's liquidity risk. When managing the liquidity reserve and its included assets, the following influencing factors need to be taken into account: Firstly, the banking organisation itself, with its business model, funding structure and related types of risk; secondly, national and international regulatory requirements have to be fulfilled and lastly, financial market behaviour and its participants need to have carefully watched and anticipated, in order to manage the risk which might arise from the liquidity reserve itself.
Keywords: G18; G20; G24; G28; 330; Asset Liability Management; Liquidity Management; Liquidity Reserve; Reserve Assets